(untitled) (Bioresearch Communications, 2021)
A total of twenty nine species of fungi namely Aspergillus aculeatus Lizuka, A. flavus Link, A. fumigatus Fresenius, A. niger Van Tiegh, A. nidulans Eidam, A. subramanianii Visagie, Frisvad & Samson, A. tamariiKita G., A. toxicarius Murak, A. wentii Wehmer, Curvularial unata (Wakker) Boedijn, Colletotrichum gloeosporioides (Penz.) Sacc., C. gossypii Southw., Chaetomium globosum Kunze., Fusarium moniliforme J. Shelden, F. nivale (Fr.) Sorauer, F. oxysporum Schlechtendal, F. fujikuroi Nirenberg, F. solani(Mart.) Sacc., Lasiodiplodiatheobromae (Pat.) Griffon & Maubl., Meyerozyma guilliermondii (Wick.) Kurtzman & M. Suzuki., Mucor sp. P. Micheli ex L., Penicillium aculeatum Raper& Fennell, Penicillium citrinum Thom, Rhizoctonia solani Khun., Rhizopus stolonifer (Ehrenb.) Vuill., Rhizopus oryzae Went & Prins. Geerl., Rhizo mucor sp. Luce t & Costantin, Syncephalastrum racemosum Cohn and Trichoderma viride Pers. were found to be associated with the seeds of 14 varieties viz. CB-1 to CB-14 of cotton. Seed quality analysis showed that percentage of pure seeds, germination, moisture, seedling mortality and associated fungi with different varieties of cotton seeds varies from 97.08-99.92%, 80-93%, 10-11.3%, 16.05-50.30% and 24-78.0% respectively. Present study deals with estimation of interrelationship between some quality factors through correlation and regression analysis are important for the assessment of seed quality. There were negative correlations between seedling mortality and purity percentage and between germination rate and fungus frequency. On the other hand, positive correlations were found between germination rate and purity percentage, between seedling mortality and fungus frequency, between purity percentage and fungus frequency, between germination rate and seed moisture and between fungus frequency and seed moisture. CB 8 was superior from the other cotton variety as it showed higher physical purity of seed (98.41%), higher seed germination (92%), lower fungal incidence (24%) and lower mortality of seedling (23.91%). Bioresearch Commu. 8(1): 1061-1067, 2022 (January)